Pregnancy, Birth and the COVID-19 Pandemic in the United States. Issue 5 (3rd July 2020) - Davis-Floyd, Robbie; Gutschow, Kim; Schwartz, David A
ABSTRACT: How quickly and in what ways are US maternity care practices changing due to the COVID-19 pandemic? Our data indicate that partners and doulas are being excluded from birthing rooms leaving mothers unsupported, while providers face lack of protective equipment and unclear guidelines. We investigate rapidly shifting protocols for in- and out-of-hospital births and the decision making behind them. We ask, will COVID-19 cause women, families, and providers to look at birthing in a different light? And will this pandemic offer a testing ground for future policy changes to generate effective maternity care amidst pandemics and other types of disasters?